Note d’information complémentaire concernant l’opération de fouille préventive sur le site de l’amphithéâtre de Saintes (Charente-Maritime) - Karine Robin; Victorine Mataouchek (Gallia)
This notice follows the recent publication of an article by Bastien Gissinger concerning the amphitheatre in Saintes. We would like to make corrections, which we feel are relevant to the context and scientific issues at stake.